A new species of planthopper in the genus Paraphenice (Hemiptera: Derbidae: Otiocerinae) from palms in eastern Madagascar - Bahder, Brian W.; Stroiński, Adam; Łukasik, Piotr; Bartlett, Charles R.; Pilet, Fabian; Hasinjaka, Rasolondalao Harin’hala (Zootaxa, 2024)
A survey of planthoppers associated with palms in Madagascar was initiated to assess putative vectors of a phytoplasma causing palm decline. Here a derbid collected from a Chinese fan palm (Livistona chinensis) is described as Paraphenice fluctus sp. n., with supplemental molecular data for the cytochrome c oxidase subunit I (COI) gene, 18S rRNA gene, and D9–D10 expansion region of the 28S rRNA gene.